The 'GALS' locomotor screen. Issue 10 (October 1992) - Doherty, M; Dacre, J; Dieppe, P; Snaith, M
Abstract : The locomotor system is complex and difficult to examine. A selective clinical process to detect important locomotor abnormalities and functional disability could prove valuable. A screen based on a tested 'minimal' history and examination system is described, together with a simple method of recording. The screen is fast and easy to perform. As well as providing a useful introduction to examination of the locomotor system, the screen includes objective observation of functional movements relevant to activities of daily living. Its inclusion in the undergraduate clerking repertoire could improve junior doctors' awareness and recognition of rheumatic disease and general disability. It could also provide a valuable screening test for use in general practice.